A Festa do Zé Bagunça em Bueno Brandão-MG (1982-2016): histórias e memórias - Alexandre, João Marcos (2017)
This essay is aimed at studying of the Arraiá of Zé Bagunça, that has been happening since 1982 in the city of Bueno Brandão. It tends to understand the Party, its dynamics and contemporaneity and statements between contents of power as well as its articulations and relations with the city in its incessant valorization and investments on the tourist market and the popular culture. Its organizational structure is made by three chapters. The first intends to point out the dynamics of the public power of the city in investing on the tourism and explore the different cultural practices like the old parties of Zé Bagunça. The second chapter points out the origins of the June parties of the neighborhood, its characteristics and the trajectory of its party man’s life – José Coutinho dos Santos Júnior. It also deals with the differents cultural practices that exist in the event and the tentions and reinventions of and in the party , materialized in the dialogue that the differents social segments keep with the cultural demonstrations like congada, catira, quadrilha and São Gonçalo dance. The oral history methodology was used where you analyse the experiences, sensitivities and the memories of the different social ways of the party. The third chapter intends to point out the process of incorporation of the party spread and its increasing involvement with the tourism and marketing. The development of the dissertation finds references in the sources consulted and in the reading and interpretation of the theorics of the social history, just like: Canclini (2011), Hall (2003) and Hobsbawn (2015)